Edukasi Pencegahan Risiko Cedera dan Pelatihan Mobilisasi Aman pada Lansia di Panti Sosial Tresna Werdha Gau Mabaji Gowa: Injury Risk Prevention Education and Safe Mobilisation Training for the Elderly at the Tresna Werdha Gau Mabaji Gowa Social Home - Hermadin, Hermadin; Hamka, Hamka; Sumarmi, Sumarmi; As, Asrar (Journal of Sustainable Community Practices, 2026)
The aging process triggers a decline in neuromuscular function, significantly increasing the risk of falls among the elderly with potentially fatal physical and psychological impacts. This community service activity aims to improve health literacy and mobilization independence for 21 elderly residents at PSTW Gau Mabaji Gowa in September 2025. The implementation method began with functional status screening using the Time Up and Go (TUG) Test, followed by module-based interactive health education and gradual training on the use of mobility aids. The TUG Test results revealed that the majority of respondents (57.15%) fell into the High Fall Risk category due to physical weakness, comorbidities, and nursing home environmental factors. However, interventions through education and therapeutic communication proved effective in increasing the elderly's confidence in using assistive devices and reducing psychological barriers such as fear of falling. This program successfully enhanced the knowledge and practical skills of the elderly in safe mobilization; thus, the synergy between education and environmental modification is crucial to maintaining their quality of life, ensuring they remain active and safe within the facility. Abstrak Proses penuaan memicu penurunan fungsi neuromuskular yang secara signifikan meningkatkan risiko jatuh pada lansia dengan dampak fatal secara fisik maupun psikologis. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan literasi kesehatan dan kemandirian mobilisasi bagi 21 lansia di PSTW Gau Mabaji Gowa pada September 2025. Metode pelaksanaan diawali dengan skrining status fungsional menggunakan instrumen Time Up and Go (TUG) Test, yang dilanjutkan dengan edukasi kesehatan interaktif berbasis modul serta pelatihan penggunaan alat bantu gerak secara bertahap. Hasil penilaian TUG Test mengungkapkan bahwa mayoritas responden (57,15%) berada pada kategori Risiko Jatuh Tinggi akibat kelemahan fisik, penyakit penyerta, dan faktor lingkungan panti. Namun, intervensi melalui edukasi dan komunikasi terapeutik terbukti efektif meningkatkan kepercayaan diri lansia dalam menggunakan alat bantu serta menurunkan hambatan psikologis berupa fear of falling. Program ini berhasil meningkatkan pengetahuan dan kemampuan praktis lansia dalam mobilisasi aman, sehingga sinergi antara edukasi dan modifikasi lingkungan menjadi sangat krusial untuk menjaga kualitas hidup lansia agar tetap aktif dan aman di lingkungan panti.